Reduction of Tin(II) and Antimony(III) in the 1-Ethyl-3-methylimidazolium Tetrafluoroborate Ionic Liquid - YANG, WENZHONG; CANG, HUI; TANG, YONGMING; WANG, JINTANG; SHI, YUANXIANG (Asian Journal of Chemistry, 2010)
The reductions of Sn(II) and Sb(III) were studied in the air-stable (1-ethyl-3-methyl imidazolium tetrafluoroborate) [EMIm]BF4 ionic liquid at room temperature. Linear sweep voltammetry (LSV) results show that reductions of Sn(II) and Sb(III) on Pt electrode are electrochemically irreversible behaviour. Diffusion coefficients for Sn(II) and Sb(III) were calculated from LSV data. The Stokes-Einstein products for Sn(II) and Sb(III) are 7.27 × 10-10 and 2.35 × 10-10 g cm s-2 K-1. These values indicate that the formation of simpler Sn(II) chloro complex species and higher Sb(III) chloro complexes in the [EMIm]BF4. The electrodeposition of Sn(II) and Sb(III) was investigated on Pt electrode. Energy dispersive spectroscope (EDS) results show that tin and antimony can be reduced to their metals on Pt electrode simultaneously.